FAKTOR-FAKTOR YANG MEMENGARUHI KURS RUPIAH - Raja Rian Ritonga; Hijri Juliansyah; Murtala; Noviami Trisniarti (Jurnal Ekonomi Pertanian Unimal, 2025)
This study aims to analyze the influence of world CPO prices, money supply, and inflation on the rupiah exchange rate partially or simultaneously in Indonesia from 1993-2023. The research method used in this study is the Autoregressive Distributed Lag (ARDL) Model. This study found that in the short term, world CPO prices have a negative and significant effect on the rupiah exchange rate in Indonesia, while the money supply and inflation have a positive and significant effect on the rupiah exchange rate in Indonesia. In the long term, world CPO prices and inflation have a negative and insignificant effect on the rupiah exchange rate in Indonesia, while the money supply has a positive but insignificant effect on the rupiah exchange rate in Indonesia.